YOUTH COUNSELING WITH THE USE OF LAI FRUIT AS AN IMMUNE ENHANCER FOR COASTAL ADOLESCENTS - Yulianti, Ika; Doris Noviani; Qolbi Nur J; Cut Wilda Safira; Nur Aisyah Fitriani; Yunika Ayu Hardani; Hardilla Jamaina Sulmi (Journal of Social Comunity Services, 2024)
General Background: Nutritional deficiencies among adolescents can significantly impact immune function, particularly in coastal areas where access to diverse food sources may be limited. Specific Background: Kalimantan Lai Fruit (Durio kutejensis) is a local resource that has received little attention regarding its nutritional potential and health benefits. Knowledge Gap: Despite its availability, there is insufficient data on the fruit's nutrient composition and its role in enhancing immunity among adolescents. Aims: This study aims to analyze the nutritional content of Kalimantan Lai Fruit and evaluate its impact on the immune health of adolescents in coastal communities. Results: Through systematic sampling and laboratory analysis, findings revealed that Lai Fruit is rich in essential nutrients, including high levels of protein, healthy fats, vitamin C, and iron. These nutrients are crucial for promoting health and enhancing the immune system. Novelty: This research not only provides a comprehensive analysis of the nutritional profile of Lai Fruit but also includes an extension program that successfully increased knowledge among children about immunity and healthy lifestyles. Implications: The results underscore the potential of Lai Fruit as a valuable dietary source for improving adolescent nutrition and health. Furthermore, the study contributes to community health initiatives by promoting the integration of local food resources into dietary practices, thereby addressing nutritional deficiencies and fostering healthier lifestyles among adolescents in coastal areas.